INTEGRASI NILAI KEARIFAN LOKAL MELALUI SATWA I LUTUNG TEKEN I KEKUE DALAM PEMBELAJARAN BAHASA BALI DI SEKOLAH DASAR - I Wayan Sujana; Ni Luh Ayu Rosita Dewi; Umniyati Rizka; Ni Kadek Sinta Lascahya Puji (STKIP Subang, 2026)
This study was motivated by the importance of preserving local wisdom through Balinese language learning in elementary schools to develop students’ character. The study aimed to examine the integration of local wisdom values through the folktale I Lutung Teken I Kekue in Balinese language learning. This study employed a qualitative approach with a descriptive design. Data were collected through observation, interviews, and documentation involving Balinese language teachers and sixth-grade elementary school students. The findings showed that the folktale I Lutung Teken I Kekue contained moral, social, and cultural values, including responsibility, accuracy, solidarity, the use of the Balinese language, and the preservation of the mesatua tradition. It was concluded that Balinese folktales are effective learning media for strengthening students’ character based on local wisdom